Military and demographic inter-linkages in the context of the Lithuanian sustainability - Meidutė-Kavaliauskienė, Ieva; Dudzevičiūtė, Gitana; Maknickienė, Nijolė (Journal of Business Economics and Management, 2020)
This paper aims at investigating military and demographic inter-linkages in the context of the Lithuanian sustainability. The investigation combines three important economic aspects such as demographic, military and sustainable development. The authors have revealed that demographic trends should be seen as a necessary conditions for ensuring the functioning of the military sector contributes to public security and sustainable development in general. Correlation and stepwise regression analysis, also Monte Carlo forecasting method have been applied for this purpose. Research results have revealed statistically significant interrelationship between military personnel as a share of total labour force and population growth rate, population median age, total fertility rate as well as birth rate. Moreover, Monte Carlo forecasting method allowed revealing for the next 10 years a steady slight increase in armed forces personnel, stable population growth rates, a rapid aging process and a slight decline of total fertility rate. Military and demographic estimations and future projections allow government to incorporate information into planning and sustainable development policy. The insights from this research may contribute to implementing the goals of sustainable development related to eradication of poverty, inequality, social exclusion, improvement in education, well-being and employment and tackling climate change.